BETON RAMAH LINGKUNGAN DENGAN CANGKANG TELUR SEBAGAI PENGGANTI SEBAGIAN SEMEN - Rizky Febriani Pohan; Muhammad Rahman Rambe (Jurusan Teknik Mesin Universitas Pattimura, 2022)
The world of construction is progressing very rapidly. The higher the need for infrastructure development, the energy absorption to support these activities will certainly be very large. To minimize this need, it is necessary to have innovations that can reduce the production of materials, such as cement. Therefore, it is necessary to have an alternative to take advantage of wasted waste such as egg shells to be used as a partial or complete substitute for cement, especially as a mixed material in the manufacture of concrete. This study aims to maximize the use of chicken egg shell waste for concrete mixtures. Egg shell powder to be added as a partial substitute for cement is made with a composition variation of 0%; 2.5%; 5%; 7.5%; 10%. Where each variation is made into 3 samples, so that the total sample is 15 samples and the compressive strength of the concrete is tested after 28 days. Based on the results obtained, it can be concluded that the mixture of concrete with egg shells at a percentage of 2.5% is called the optimum state. The optimum condition is a condition where the compressive strength of the resulting concrete is greater and maximum when used to make environmentally friendly concrete.